Identifikasi Karakteristik Lahan Pemakaman TPBU di Kota Tangerang Selatan - Forina Lestari; Muhammad Rizky Harun; Ira Indrayati (P4W LPPM IPB, 2022)
Cemetery is one of the space requirements that also needs to be considered in urban management. Because apart from burial activities, burial grounds can also function as urban green open spaces. Private Cemetery Parks (TPBU) currently have not received the attention of stakeholders, especially in urban areas. As a result, many TPBUs are not well organized in terms of management, location, and access to available facilities. South Tangerang City has approximately 150 TPBU whose ownership and management are carried out by social/community institutions. The purpose of this study is to identify the characteristics of private cemetery (TPBU) including management, location, land use, road network, funeral service coverage, funeral facilities, and infrastructure. The research method used is data collection through observation and interviews with grave managers. After that, descriptive analysis was carried out on several criteria, namely location and accessibility, status, and management of the cemetry, and available facilities. The results of this study also explore strategies for TPBU funeral management including the management system, as well as infrastructure that needs to be considered in the management of TPBU funerals in South Tangerang City.